A Review Of Elements For Assessment Of E-learning Readiness In Libya Universities. - Mohamed Munser Saleh; Fauziah Abdul Wahid (Khalsa Publications, 2024)
The e-learning is developing rapidly in the world nowadays, where technology has replaced the traditional educational approach in many universities around the world. This is because e-learning can save time and cost in educational approach as a whole. This phenomenon has spread to many developing countries like Libya with the main aim to improve the educational system. However, there seems to be lack of study on the readiness of implementing e-learning in Libya universities. Therefore, this paper will shed some light on elements needed to be evaluated to study the e-learning implementation readiness in Libya universities.